The monkey and the organ-grinder: a timeless relationship between book authors and their publishers. - McCracken, Donal P. (Critical Arts: A South-North Journal of Cultural & Media Studies, 2015)
This article focuses on subtle and sometimes not-so-subtle discrimination authors experience because of their enforced relationship with their publisher. Giving pertinent examples, the article asserts that this is no new phenomenon, and that the dominant publisher-over-author nexus stretches back at least to the Victorian era. Six distinct problem areas are identified and discussed, the first being the invariably murky manuscript review process. This is followed by the usually one-sided (from the publisher’s point of view) disclaimers inherent in the publication contract. The frequently mendacious nature of the publication schedule is discussed, as is the habitual issue surrounding royalties and authors’ complementary copies. The ‘fairy tales’ surrounding print runs have touched upon as well as (often most exhausting for the author) the demand for additional material to broaden the appeal and thus the sales of the book.